Vibrational Dynamics of Pd-Ni-P Bulk Metallic Glasses: a Local Pseudopotential Study - Suthar, Punit H; Gajjar, P N (Communications in Physics, 2022)
In the present paper, Phonon modes and elastic constant of three different concentrations of PdxNi1-xP (Pd64Ni16P20, Pd40Ni40P20 and Pd16Ni64P20) bulk metallic glass are calculated using (1) Hubbard-Beeby (HB) and (2) Takeno-Goda (TG) approach along with our well established local model potential. The Hartree (H), Farid et al (F) and Sarkar et al (S) local field correlation functions (LFCF) are employed to examine the effect of the screening function on the collective dynamics of Pd-Ni-P bulk metallic glasses. Results are also reported for phonon dispersion curve, propagation elastic wave and elastic properties viz: bulk modulus BT, modulus of rigidity G, Poisson’s ratio ξ, Young’s modulus Y, Debye temperature ƟD. However, the calculated elastic constants results agree well with other theoretical and available experimental data.